Same‐day or next‐day sentinel node biopsy after lymphoscintigraphy for melanoma using 99mTc‐labelled antimony sulphide colloid. Issue 13 (21st August 2020) - Thompson, J. F.; London, K.; Uren, R. F.; Pennington, T. E.; Saw, R. P. M.; Lo, S. N.
Abstract : Background: Two recent publications have reported that a shorter interval between preoperative lymphoscintigraphy and sentinel node biopsy (SNB) is associated with improved survival of patients with primary cutaneous melanoma. The aims of this study were to analyse prospectively collected survival data for patients who had SNB on the same day as lymphoscintigraphy or the day after; and to assess tracer migration from sentinel nodes to second‐tier nodes after lymphoscintigraphy on the previous day. Methods: Outcome data were obtained for patients who had lymphoscintigraphy and SNB on the same day (time interval less than 8 h) or the next day (interval more than 16 h). In a separate prospective cohort, same‐day and next‐day lymphoscintigraphic images of sentinel nodes and second‐tier nodes were compared. Results: Following lymphoscintigraphy, 2848 patients had same‐day and 3328 had next‐day SNB. Survival outcomes did not differ between these groups. In a prospectively studied cohort of 30 patients, none had significant tracer migration from sentinel nodes to second‐tier nodes on imaging the following day. Conclusion: No difference in survival after same‐ or next‐day sentinel node biopsy is seen when 99m Tc‐labelled antimony sulphide colloid is used. This may be because of less tracer migration to second‐tier nodes. Abstract : If 99m Tc‐labelled antimony sulphide colloid is used for lymphoscintigraphy in patients with melanoma, accurate intraoperative identification of sentinel nodes (SNs) during surgery the following day is possible and reliable using a γ detection probe because significant onward migration of tracer from SNs to second‐tier nodes does not occur overnight. Consistent with this finding, no difference in melanoma‐specific or overall survival was observed between patients having same‐day or next‐day SN biopsy procedures. However, the situation may be different when 99m Tc‐labelled albumin nanocolloid is the tracer used for preoperative lymphoscintigraphy; SN biopsy as soon as possible after lymphoscintigraphy is likely to be required if accurate intraoperative SN identification is to be achieved. Use nanocolloid same day only? Abstract : Antecedentes: Dos publicaciones recientes han señalado que reducir el intervalo entre la linfografía isotópica preoperatoria y la biopsia del ganglio centinela ( sentinel node biopsy, SNB) se asocia con una mejor supervivencia en pacientes con melanoma maligno primario. Los objetivos de este estudio fueron los siguientes: (1) analizar los datos de supervivencia recogidos prospectivamente en pacientes en los que se realiza la SNB el mismo día o al día siguiente de la linfografía isotópica, y (2) evaluar la migración del marcador desde los ganglios centinela a los ganglios de segundo nivel a partir de la linfografía del día anterior. Métodos: Se analizaron los resultados de los pacientes a los que se realizó una linfografía isotópica y la SNB el mismo día (intervalo de tiempo < 8 h) o al día siguiente (intervalo > 16 h). En una cohorte prospectiva diferente, se compararon las imágenes de los ganglios centinela y de los ganglios de segundo nivel en linfografías isotópicas realizadas el mismo día o al día siguiente. Resultados: Tras la linfografía isotópica, se realizó la SNB el mismo día en 2.848 pacientes y al día siguiente en 3.328 pacientes. No hubo diferencias en la supervivencia entre ambos grupos. En una cohorte de 30 pacientes estudiada de forma prospectiva, no hubo migración significativa del trazador de los ganglios centinela a los ganglios de segundo nivel en las imágenes obtenidas al día siguiente. Conclusión: La mejor supervivencia que se obtiene cuando se realiza la SNB poco después de la linfografía isotópica podría explicarse por una diferencia en la migración del trazador a los ganglios de segundo nivel entre los dos marcadores utilizados: nanocoloide de albúmina humana o coloide de sulfuro de antimonio, ambos marcados con 99mTc. En este estudio y con este último marcador, no se observó migración a ganglios de segundo nivel durante la noche.